An STPA Safety Analysis Case Study of a Collaborative Robot Application. Issue 1 (2021) - Adriaensen, A.; Pintelon, L.; Costantino, F.; Gravio, G. Di; Patriarca, R.
Abstract: The technology for collaborative robots and the way these technologies are used in current socio-technical work systems are rapidly evolving in industrial applications. In the absence of prescribed safety assessment methods from normative standards, this paper explores the capabilities of an STPA analysis for the socio-technical behaviour of collaborative robot applications. We applied the STPA to a collaborative robot with a heavy-load manipulating arm and gripper, mounted on an AGV-type mobile base. The scope of the analysis is limited to a single AGV mode controller. It explores the systems thinking capabilities of STPA for the safety analysis, from which the principles can be applied to several types of collaborative robot applications.